ORGANIZATIONAL CULTURE AND INTRAPRENEURSHIP EMPLOYEE OF THE IMPACT ON WORK DISCIPLINE OF EMPLOYEES IN BRANGKAL OFFSET - Rahmah, Mirhamida; Fatmah, Dinda (JURNAL ILMU MANAJEMEN DAN BISNIS, 2019)
Discipline is very important for organizational growth, used primarily to motivate employees to be able to discipline themselves in carrying out work both individually and in groups. Besides that, the discipline is beneficial to educate employees to comply with and enjoy the rules, procedures, and policies that exist, so that they can produce good performance.The objectives of this study are: 1) To find out whether organizational culture and employees intrapreneurship have a partial effect on work discipline of employees in Brangkal Offset Mojokerto 2) To find out whether intrapreneurship organizational culture and employees simultaneously influence the work discipline of employees in Brangkal Offset Mojokerto. The population in this study were 35 people, this study used population research. In sampling from 35 employees, 100% were taken as subjects or respondents.Based on the results of the regression analysis it was found that first that: 1) There is a partial influence between intrapreneurship organizational culture and employees on employee discipline in Brangkal Offset Mojokerto. 2) There is a simultaneous influence between intrapreneurship organizational culture and employees on work discipline of employees in Brangkal Offset Mojokerto.